2014
DOI: 10.1080/15388220.2014.922472
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Adolescent Adjustment: Does School Belonging Matter?

Abstract: Recent research highlights the role of peer victimization in students’ adjustment across a variety of domains (e.g., academic, social), but less often identifies potential mediating variables. In the current study, we tested for direct effects from peer victimization to adolescents’ academic behavior and alcohol use, as well as indirect effects through school belonging. Adolescents from two large samples (middle school: N = 2,808; high school: N = 6,821) self-reported on peer victimization, school belonging, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 54 publications
1
31
0
2
Order By: Relevance
“…Approaches that reduce prejudice and promote sexual equality, such as Gay-Straight alliances, likely both reduce bullying against SMY and empower them to cope effectively by increasing sense of belonging in the school (Wormington et al, 2016). Adults working in schools do not always recognize homophobic language commonly used by adolescents (McCabe, Dragowski, & Rubinson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches that reduce prejudice and promote sexual equality, such as Gay-Straight alliances, likely both reduce bullying against SMY and empower them to cope effectively by increasing sense of belonging in the school (Wormington et al, 2016). Adults working in schools do not always recognize homophobic language commonly used by adolescents (McCabe, Dragowski, & Rubinson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among several school climate indicators, school bonding is defined as the extent to which students feel close and connected to the school space and personnel (Jenkins 1997), and a higher level of school bonding was particularly predictive of reduced school delinquency and violence (Libbey 2004). Positive school bonding also mediated the relationship between peer victimization and adolescents' problematic behavioral outcomes (e.g., underage drinking; Wormington et al 2016). In addition, studies that examined school bonding as a moderator found a buffering effect such that a more positive perception of school bonding attenuates the negative links between negative personal coping strategies and negative socioemotional outcomes (Loukas and Robinson 2004).…”
Section: School Bonding As a Moderator Between Coping Patterns And Mamentioning
confidence: 99%
“…Third, we examined if the perception of school bonding moderates the relationship between the aforementioned transition. Based on previous research suggesting the positive effects of school bonding on students' social outcomes (e.g., Loukas and Robinson 2004;Wormington et al 2016), we hypothesized that a positive perception of school bonding would promote the use of a combination of adaptive coping strategies (e.g., both high problemsolving and seeking social support strategies). The findings highlight the heterogeneity and uniqueness of coping strategies adolescents employ in a non-Western context.…”
Section: Current Studymentioning
confidence: 99%
“…Bestalde, jazotzen den diskriminazioak ondorio negatiboak ekar ditzake nerabearen eskola-doikuntzan eta errendimendu akademikoan (Hood, Bradley, eta Ferguson, 2017). Ikerketa batzuen arabera, kideen arteko biktimizazioak errendimendu akademiko negatiboarekin lotura estua izateaz gainera, eskola-absentismoarekin ere badu zerikusia (Wormington, Anderson, Schneider, Tomlinson, eta Brown, 2016) baita jokaera arazoekin ere (Feldman et al, 2014); gainera, azpimarratzen da biktimizazioak eta jokaera-arazoek eskolako giro negatiboa hautemanarazten dutela, lagunak egiteko jarrera pasiboagoa erakusten dutela eta ikasketekin jarraitzeko itxaropen gutxi izaten dela (Liu et al, 2014).…”
Section: Eskola-doikuntzari Lotutako Testuinguru-aldagaiakunclassified